A dual-wavelength electrochromic film based on a Pt(ii) complex for optical modulation at telecommunication wavelengths and dark solid-state display devices. Issue 28 (29th June 2021) - Pi, Qiaozhen; Bi, Dongqin; Qiu, Dongfang; Wang, Hongwei; Cheng, Xinfeng; Feng, Yuquan; Zhao, Qian; Zhou, Mingdong
Abstract : The film prepared by oxidative electropolymerization of a cyclometalated Pt(ii ) phenylacetylide shows the independent optical modulation at 1520 nm under +1.0 V, and the long-term electrochromic behaviour at 773 nm between −0.5 and +1.6 V. Abstract : A cyclometalated platinum phenylacetylide [(L )Pt(CC–ph)] {L = 4-[ p -(diphenylamino)phenyl]-6-phenyl-2, 2′-bipyridine} has been successfully synthesized and characterized. Its oxidative electropolymerization film with a non-diffusion controlled redox behaviour and an inverse dependence of AC impedance on its thickness has also been obtained by cyclic voltammetry on the working ITO electrode. The hybrid film possesses interesting dual-wavelength electrochromic properties in visible and near-infrared spectral regions. The low-voltage-controlled near-infrared electrochromism at 1520 nm under +1.0 V exhibits a moderate optical contrast ratio (Δ T % = 49%), a fast response time (8.4 s for the coloration step and 1.1 s for the bleaching step), and high coloration and bleaching efficiency (242.0 and 232.5 C −1 cm 2 ). The solid-state display device shows a significant colour change from orange to dark-blue (Δ T % = 51%) with excellent electrochromic properties (6.5 s for the coloration step and 9.5 s for the bleaching step, and coloration and bleaching efficiencies of 203.5 and 241.3 C −1 cm 2 ) and long-term stability at 773 nm between −0.5 and +1.6 V.